Hypoglycemic and Antioxidative Effects of Eugenia Aromatica and Archidendrone Jiringa on Diabetic Rats - Shukri, Radhiah (2006)
The study conducted for 15 weeks involved 56 Sprague Dawley male rats aged three weeks that were divided into seven groups. Two control groups were normal rats and induced-diabetic rats given a basal diet, four other groups were 2 normal rat groups and 2 induced-diabetic rat groups either supplemented with a basal diet containing 5% of cloves (Eugenia aromatica) or jering (Archidendrone jiringa) respectively. The basal diet that contained Glibenclamide (3mg/kg body weight) was supplemented to the remaining one group of diabetic rats. Body weight and feed consumption were monitored weekly and daily respectively. During a 3 weeks interval, blood samples were drawn via cardiac puncture for the purpose of biochemical analysis that consisted of glutathione peroxidase (GSH-Px), catalase (CAT) and superoxide dismutase (SOD) activities; malondialdehyde (MDA) level and levels of urea, creatinine, alanine aminotransferase (AST) and aspartate aminotransferase (AST). Somatic index and histological changes of liver, heart, lung, eye, brain, kidney and pancreas of the experimental rats were also evaluated. The results observed showed a slight lowering of blood glucose level of 6.1±0.4 and 6.2±0.5 mmol/l for cloves and jering supplemented STZ-diabetic rats respectively. The body weight of the diabetic rats supplemented with the herbs was also improved with R2 value of 0.9924 and 0.9068 for jering and cloves, respectively. Weak anti-oxidative property in blood and organs was revealed with the supplementation of the herbs but was more effective in cloves. While evidence of toxicity of jering was shown mainly in the liver, kidney and heart of normal and diabetic rats, cloves was seen to be toxic to the pancreas of diabetic rats through histology. Jering-supplemented normal and diabetic groups had high cardiosomatic index with 0.51±0.11 (NJ) and 0.49±0.04 (DJ), necrotic hepatocytes and Kupffer cells of 50.5±5.0 (NJ) and 71.2±5.2 (DJ), respectively. However, toxicity effect of these herbs towards certain organs at the 5% dose given suggests that a dose-response effect need to be further studied.